2020
DOI: 10.3390/toxins12110698
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Domoic Acid Depuration in the Scallop Argopecten purpuratus and Its Transfer from the Digestive Gland to Other Organs

Abstract: Domoic acid (DA), the main toxin responsible for Amnesic Shellfish Poisoning, frequently affects the marine resources of Chile and other countries across the South Pacific, thus becoming a risk for human health. One of the affected resources is the scallop Argopecten purpuratus. Even though this species has a high commercial importance in Northern Chile and Peru, the characteristics of its DA depuration are not known. In this work, the DA depuration was studied by means of two experiments: one in controlled (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…It is known that this variability is in part due to differences in depuration velocity. Some bivalves depurate most of the toxin very quickly, as is the case for the mussels M. galloprovincialis [ 18 ], M. edulis [ 19 , 20 ], Mesodesma donacium [ 21 ], and the scallop Argopecten purpuratus [ 22 ], while other species can retain it for very long periods of time, such as the razor clam Siliqua patula [ 23 , 24 , 25 ] or the king scallop Pecten maximus [ 26 , 27 , 28 ]. Mafra et al [ 29 , 30 ] showed that the reduction in the amount of toxic cells ingested by pre-ingestive selection of the phytoplankton species can partially explain the observed differences between bivalve species, but the role of toxin absorption mechanisms in accumulation (acting after toxin ingestion) has not been sufficiently studied.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that this variability is in part due to differences in depuration velocity. Some bivalves depurate most of the toxin very quickly, as is the case for the mussels M. galloprovincialis [ 18 ], M. edulis [ 19 , 20 ], Mesodesma donacium [ 21 ], and the scallop Argopecten purpuratus [ 22 ], while other species can retain it for very long periods of time, such as the razor clam Siliqua patula [ 23 , 24 , 25 ] or the king scallop Pecten maximus [ 26 , 27 , 28 ]. Mafra et al [ 29 , 30 ] showed that the reduction in the amount of toxic cells ingested by pre-ingestive selection of the phytoplankton species can partially explain the observed differences between bivalve species, but the role of toxin absorption mechanisms in accumulation (acting after toxin ingestion) has not been sufficiently studied.…”
Section: Introductionmentioning
confidence: 99%
“…The low content of DA in P. multistriata in Peruvian waters could be one of the reasons that there has not been any detection of this toxin in scallops cultivated in Paracas Bay in the framework of the Molluscan Shellfish Control Program run by SANIPES. A second reason could be the rapid DA depuration of this bivalve in the natural environment as has been demonstrated by Álvarez, et al [70] in scallops cultivated in Tongoy Bay, Chile. However, the information provided by this work should be taken into consideration in the development of the Molluscan Shellfish Control Program ran by SANIPES [71].…”
Section: Discussionmentioning
confidence: 87%
“…Due to the blooms of domoic acid-producing species of the genus Pseudo-nitzschia and the low depuration rate of P. maximus [ 14 , 15 ], the domoic acid concentration in this scallop is usually above the regulatory limits (20 µg of domoic acid g −1 ) in many areas [ 16 ]. There are other scallop species ( Placopecten magellanicus and Argopecten purpuratus ) that do not show this slow domoic acid depuration [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Domoic acid in bivalves is mostly unmetabolized and is excreted unchanged [ 10 ]. In many bivalves, including the king scallop, the digestive gland is the main organ of accumulation of domoic acid [ 10 , 14 , 15 , 17 , 19 , 20 ]. In the digestive gland of P. maximus , domoic acid was found to be present in the cytosol in soluble form [ 21 ], therefore Mauriz and Blanco [ 21 ] suggested that the lack of an efficient membrane transporter could be the cause of the low depuration rate.…”
Section: Introductionmentioning
confidence: 99%